Alternative operators investing in NGNs: A causal analysis of the case in Spain - Fernando Herrera-González; Gonzalo García-Arribas (International Telecommunications Society (ITS), 2014)
The telecommunications market was completely open to competition in 1998 in Spain, as in most EU countries. The model for the liberalization of the market was based on the regulated use of the incumbent operators' network, so that new entrants could initially use these resources to allow for a soft entry in the market, by climbing a 'ladder of investment'. However, as late as 2011, no entrant operator had gone beyond the Unbundled Local Loop deploying its own access network. This changed in Spain in 2012, when Jazztel decided it would invest in deploying Fibre-to-the-Home. Later, Orange and Vodafone announced that they have reached an agreement to share the deployment of fibre to 6 Millions of households. This phenomenon has coincided in time with the lack of regulated wholesale access on Telefónica FTTH network for speeds above 30 Mbps. In this paper, we show the causality between both events (lack of actual regulated wholesale access to the fibre, deployment by alternative operators), by understanding competition as a process, in the Hayekian and Schumpeterian tradition.
Keywords: 330